ANALISIS SUMBER-SUMBER PENDAPATAN PETANI DI DESA KEPENGHULUAN MUMUGO KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Sari, Novita; Aulia, Ando Fahda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine farmersâ income sources in Kepenghuluan Mumugo Village Tanah Putih Sub District Rokan Hilir District. The sample in this study was 67 farmers who grew pineapples and oil palm either in joining or separate systems. The technique in collecting data used questionnaire then the data were analyzed using descriptive quantitative analysis, analysis of farming business and percentage contribution of farming analysis. Based on the results of data processing, it can be concluded that (1) pineapple farming has a greater level of contribution income, accounted for Rp. 38.850.000,- /1 Ha/ Year or 74,04% compared to oil palm farming, generated income of Rp. 13.620.000,-/1 Ha/ Year or 25,96% of the total net income. (2) Kepenghuluan Mumugo Village Tanah Putih Sub District Rokan Hilir District mostly located on peat land structure, thus affecting the productivity of oil palm, in addition to the value of the selling price of palm oil which tends to be unstable. Instead, pineapple farming was suitable on peat land, and also the demanded of pineapple fruits continued to increase which made an increasing tendency in the value of the selling price of pineapple fruits.Keywords : Area of land, Financial capital, Workers, Prices